THE PERFORMANCE OF VIRTUAL LABORATORY OF MEMBRANE SYNTHESIS VIA PHASE INVERSION AS PRE-PRACTICAL GUIDELINE IN A SEPARATION CHEMISTRY COURSE - Reza, Muhammad; Nupus, Nizawaton; Mayasri, Adean; Sabrina, Sabrina (Chimica Didactica Acta, 2025)
The development of virtual laboratory(VL) has been widely used in secondary school teaching, notably science education. However, the development of VLspecifically for university-level education remains quite limited. In addition, in some practical disciplines, such as membrane-based separation chemistry, both lecturers and students face restrictions in equipment and resources. As a result, the goal of this study is to develop a VL for membrane synthesis practicum utilizing the phase inversion approach that can also be utilized in separation chemical practicum. In addition, the researchers assessed the amount of legitimacy and user response to VL media, specifically among students. This work follows research and development based on ADDIE (Analysis, Design, Development, Implementation, and Evaluation) framework. The first phase is begun with an analysis (via interviews) to investigate the lecturers issues and needs. Consequently, the analysis confirmed that the development of VL in separation chemistry is very essential. The researchers used feedback from the lecturer during the design stage, namely while gathering the material and presentation of VL to create the storyboard. Then, three experts confirmed the draft created during the development stage, declaring it highly validwith a proportion more than 85%. Face validity and construct validity took major revision to achieve 100% of highly valid. Following the revision steps of draft I (initial version) based on the validation results, draft II (revised version) was created for restricted testing with users (students), and the results revealed a very good response, with more than 90% of students providing feedback ranging from agree to highly agree. Their responses represent the impact received from VL, particularly in digital literacy, building critical and creative thinking, and learning flexibility. Some suggestions for enhancement, particularly the usage of foreign languages in VL, will be considered in the final stage. Thus, the VL can be recommended for use in membrane synthesis experiments in the separation chemistry course.